Edukasi dan Pelayanan Kesehatan Terhadap Pencegahan Stunting Di RW 06 Rt 01 Dusun Kulolu Kelurahan Ganti Kecamatan Banawa Kabupaten Donggala Provinsi Sulawesi Tengah - Sabir Sabir; Chaerunisac Ramadhani; Megawati Megawati; Nur Fathiyyah; Nurhijrah Nurhijrah; Nirmala Sani Putri; Ni Wayan Margani; Uswatun Hasanah; Melisa Aprilia Soelo; Stela Miracle Songko; Enjelina Tangka’a; Moh. Tirta Setiahadi (Civiliza Publishing, 2025)
Stunting is still a public health problem that has an impact on the quality of human resources, especially in rural areas. In addition to stunting, environmental and lifestyle-based diseases such as vomiting and hypertension are also health challenges that need attention. This Real Work Lecture (KKN) activity aims to increase the knowledge, awareness, and healthy living behavior of the community in the prevention of stunting, vomiting, and hypertension in RW 06 RT -1 Kulolu Hamlet, Ganti Village, Banawa District, Donggala Regency, Central Sulawesi Province. The method of implementing activities includes assessing the condition of the community through the creation of garbage cans. The results of the activity show that there is an increase in public knowledge related to balanced nutrition, environmental sanitation, disease prevention and fish processing. A medical examination found several cases of hypertension that required follow-up. Educational activities are running effectively with a community participation rate of 65-71%.